Chronic disease management in emergency department patients presenting with dyspnoea. (17th September 2020) - Jones, Peter; Kelly, Anne‐Maree; Keijzers, Gerben; Klim, Sharon; Holdgate, Anna; Graham, Colin A; Craig, Simon; Kuan, Win Sen; Laribi, Said; ,
Abstract: Objectives: Guideline recommended treatments for chronic conditions are thought to reduce ED presentations. Method: We used data from 1958 ED patients with dyspnoea to describe medication use in patients with chronic conditions. Results: A total of 1233 (63.5%) patients had one or more of: chronic obstructive pulmonary disease 547 (28%), asthma 454 (23%), atrial fibrillation 368 (19%) or heart failure 401 (21%). Approximately, 70% were prescribed appropriate preventative medication for their chronic condition when they presented to ED with dyspnoea. Conclusion: Prescription of guideline recommended therapies for chronic conditions in patients presenting to the ED in Australasia with acute dyspnoea is similar or higher than reported previously.